2016
DOI: 10.3171/2015.4.spine15239
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of clinical outcomes for patients diagnosed with skin cancer spinal metastases

Abstract: OBJECT Surgical procedures and/or adjuvant therapies are effective modalities for the treatment of symptomatic spinal metastases. However, clinical results specific to the skin cancer spinal metastasis cohort are generally lacking. The purpose of this study was to systematically review the literature for treatments, clinical outcomes, and survival following the diagnosis of a skin cancer spinal metastasis and evaluate prognostic factors in the context of spinal skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…In this study, 460 (79.31%) patients received palliative surgery including 290 posterior laminectomy, 155 subtotal corpectomy, and 15 subtotal corpectomy combined with microwave ablation and vertebroplasty. Most of them presented severe pain and spinal instability but the general conditions were good with KPS score more than 60 and Frankel score in D and E. The revised Tokuhashi score have suggested that surgery only be considered in patients with a life expectancy of more than 6 months, meaning that patients, especially those with aggressive primary tumor metastasis, are ineligible for surgical symptom palliation. However, in this multicenter case series, lung cancer was the most common metastasis, as seen in 198 patients.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, 460 (79.31%) patients received palliative surgery including 290 posterior laminectomy, 155 subtotal corpectomy, and 15 subtotal corpectomy combined with microwave ablation and vertebroplasty. Most of them presented severe pain and spinal instability but the general conditions were good with KPS score more than 60 and Frankel score in D and E. The revised Tokuhashi score have suggested that surgery only be considered in patients with a life expectancy of more than 6 months, meaning that patients, especially those with aggressive primary tumor metastasis, are ineligible for surgical symptom palliation. However, in this multicenter case series, lung cancer was the most common metastasis, as seen in 198 patients.…”
Section: Discussionmentioning
confidence: 84%
“…18, 19 ‘High’ was assigned to studies that were Class of Evidence (CoE) I or II, and the true effect could be confidently assumed to be close to the estimated effect. ‘Low’ was assigned to studies that were Class III or IV, and the true effect may have been significantly different than the estimated effect.…”
Section: Methodsmentioning
confidence: 99%
“…‘Insufficient’ was assigned if there was very little confidence in the estimated result, no evidence, or too little evidence to estimate an effect. 19 The quality could be downgraded if the evidence was indirect, results were inconsistent, there were no a priori subgroup analyses or the effect estimates were imprecise. Conversely, overall estimation of quality could be upgraded if the magnitude of effect was large.…”
Section: Methodsmentioning
confidence: 99%
“…as patients with lower life expectancies are liable to have complication profiles that far outweigh any potential benefit of surgery. Unfortunately, this means that many patients, especially those with metastases secondary to aggressive primary pathologies, such as lung cancer, pancreas cancer, and melanoma, are ineligible for surgical symptom palliation due to the aggressive course of their disease (22,26,28,29,33,38,65,66). In the past decade though, multiple groups have begun to publish the results of patients with degenerative spine pathologies treated with MIS techniques.…”
mentioning
confidence: 99%